Ni/Al2O3/4H-SiC structure for He++ energy detection in RBS experiments. (18th October 2016) - Kaufmann, I.R.; Pick, A.; Pereira, M.B.; Boudinov, H.I.
Abstract: Epitaxial SiC device have been tested as detector for Rutherford Backscattering Spectroscopy (RBS). The device was fabricated on a commercial 4H-SiC epitaxial n-type layer grown onto a 4H-SiC n + type substrate wafer doped with nitrogen. Aluminum oxide with a thickness of 1 nm was deposited by Atomic Layer Deposition and 10 nm of Ni were deposited by sputtering to form the Ni/Al 2 O 3 /SiC MIS Schottky structure. Variable temperature Current-Voltage curves were used to extract the values of real Schottky Barrier Height and ideality factor (0.61 eV and 1.19, respectively). Current-Voltage and Capacitance-Voltage characteristics were measured and compared with the curves of a commercial Si barrier detector from ORTEC. RBS data for three beam energies (1, 1.5 and 2 MeV) were collected from an Au/Si sample using the fabricated and the commercial detectors simultaneously. The energy resolution for the fabricated detector was estimated to be 76 keV.